2022
DOI: 10.3390/ijerph19052633
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology-Based Instruction during Prenatal Dental Visits Improves Perinatal Oral Health Literacy

Abstract: To improve oral hygiene education, we evaluated the perception and potential impact of microbiology-focused oral hygiene instructions (OHI) given to pregnant patients. Dental hygienists provided this supplemental education and administered Saliva-Check Mutans (SCM) tests to pregnant patients (n = 188) in Obstetrics and Gynecology (OB/GYN) settings. Patients reported their self-perceived understanding of the relationship between oral bacteria and dental disease and returned postdelivery to receive a second SCM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The experimental component of the strategy, which included demonstrating the presence of bacteria on the teeth and the effect of toothpaste in reducing them, played a significant role in the positive results, especially in reducing dental biofilm in children. Several studies have reported the impact of demonstrating the presence of dental biofilm and bacteria in the oral cavity on the oral hygiene practices of participants or their children [ 35 , 44 ]. For example, a study by Thomson et al in 2022 showed that implementing oral hygiene instructions along with microbiological explanations and demonstrations increased adherence to hygiene practices and improved understanding of the relationship between oral bacteria and dental disease among pregnant patients [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental component of the strategy, which included demonstrating the presence of bacteria on the teeth and the effect of toothpaste in reducing them, played a significant role in the positive results, especially in reducing dental biofilm in children. Several studies have reported the impact of demonstrating the presence of dental biofilm and bacteria in the oral cavity on the oral hygiene practices of participants or their children [ 35 , 44 ]. For example, a study by Thomson et al in 2022 showed that implementing oral hygiene instructions along with microbiological explanations and demonstrations increased adherence to hygiene practices and improved understanding of the relationship between oral bacteria and dental disease among pregnant patients [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the impact of demonstrating the presence of dental biofilm and bacteria in the oral cavity on the oral hygiene practices of participants or their children [ 35 , 44 ]. For example, a study by Thomson et al in 2022 showed that implementing oral hygiene instructions along with microbiological explanations and demonstrations increased adherence to hygiene practices and improved understanding of the relationship between oral bacteria and dental disease among pregnant patients [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, research shows that women may not fully understand the mechanism of transmitting caries between family members. For instance, only 36% of pregnant patients surveyed in the USA knew that a mother could infect her child [ 54 ]. This may indicate that educational interventions stressing the aetiology of caries could lead to a better understanding of the health problem and possibly motivate mothers to prevent infections [ 54 ] by eliminating such practices as cleaning a dummy with the mother’s mouth or sharing feeding utensils.…”
Section: Discussionmentioning
confidence: 99%
“…It could be expected that patients lacking knowledge of the role of bacteria in dental caries may also be unaware of the importance of regular oral hygiene practices [ 54 ]. In the presented study, the average percentage of correct answers in the relevant (i.e., time) section of OHK16 was 74.7% (±20.6%), which is a markedly better score than in the bacteria section.…”
Section: Discussionmentioning
confidence: 99%